Characterization of plasma circulating small extracellular vesicles in patients with metastatic solid tumors and newly diagnosed brain metastasis - Alberto Carretero-González; Marta Hergueta-Redondo; Sara Sánchez-Redondo; Pilar Ximénez-Embún; Luis Manso Sánchez; Eva Ciruelos Gil; Daniel Castellano; Guillermo de Velasco; Héctor Peinado (OncoImmunology)
Nearly 40% of the advanced cancer patients will present brain metastases during the course of their disease, with a 2-year life expectancy of less than 10%. Immune system impairment, including the modulation of both STAT3 and PD-L1, is one of the hallmarks of brain metastases. Liquid biopsy could offer several advantages in brain metastases management, such as the possibility of noninvasive dynamic monitoring. Extracellular vesicles (EVs) have been recently proposed as novel biomarkers especially useful in liquid biopsy due to their secretion in biofluids and their role in cell communication during tumor progression. The main aim of this work was to characterize the size and protein cargo of plasma circulating EVs in patients with solid tumors and their correlation with newly diagnosed brain metastases, in addition to their association with other relevant clinical variables. We analyzed circulating EVs in the plasma of 123 patients: 42 patients with brain metastases, 50 without brain metastases and 31 healthy controls. Patients with newly diagnosed brain metastases had a lower number of circulating EVs in the plasma and a higher protein concentration in small EVs (sEVs) compared to patients without brain metastases and healthy controls. Interestingly, melanoma patients with brain metastases presented decreased STAT3 activation and increased PD-L1 levels in circulating sEVs compared to patients without central nervous system metastases. Decreased STAT3 activation and increased PD-L1 in plasma circulating sEVs identify melanoma patients with brain metastasis.